FUNDING LIQUIDITY DYNAMICS AND ITS INFLUENCE ON BANK LENDING GROWTH: A REVIEW OF THE INDONESIAN BANKING CONTEXT - Zaenal Aripin; Lili Adi Wibowo; Maya Ariyanti (PT. Kreatif Indonesia Satu, 2024)
Funding liquidity is a crucial aspect of banking activities that influences the growth of bank credit provision. The banking context in Indonesia exhibits unique dynamics influenced by various internal and external factors. Therefore, a profound understanding of the dynamics of funding liquidity and its influence on bank credit growth is essential in creating a healthy and sustainable financial environment. This study aims to analyze the dynamics of funding liquidity and its impact on the growth of bank credit provision within the banking context of Indonesia. Thus, the research objective is to explore the factors affecting funding liquidity and their implications for bank credit provision activities. This research employs a qualitative approach by conducting a literature review of relevant sources, including journals, articles, and books discussing funding liquidity and bank credit growth. The analysis is conducted by considering various economic, financial, and regulatory factors influencing the dynamics of funding liquidity and bank credit growth in Indonesia. The research findings indicate that adequate funding liquidity significantly affects the growth of bank credit provision in Indonesia. Factors such as monetary policy, banking regulations, and financial market development play a crucial role in shaping funding liquidity and bank credit growth. With a profound understanding of these dynamics, regulators and banking practitioners can take appropriate measures to enhance financial stability and support sustainable economic growth.